A Mnemonic Based on Arranging Words on Visual Patterns; Performance Improvement Quarterly; The Cooperative Extension Service; Instant Health Information: Serving Needs of Rural Residents - Debrah Jefferson; Jim King; Greg Nolting; Jim Shaner (Journal of Applied Communications, 1988)
Reviews of "A Mnemonic Based on Arranging Words on Visual Patterns," by Francis S. Belezza; Performance Improvement Quarterly; The Cooperative Extension Service: A National Assessment, by Paul D. Warner and lames A. Christenson; "Instant Health Information: Serving Needs of Rural Residents" by Bernice A. Epstein.